A Toxidromic based Assessment of Patterns of Poisoning in a Tertiary Hospital in India - Richa Choudhury; Ritu Karoli; Dipti Agrawal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Acute poisoning is an important and common medical emergency. Acute poisoning is one of the major healthchallenges both in developing as well as developed countries 2, 3 Aim of the Study-We had conducted a studywith the objective to investigate the pattern of acute poisoning cases by utilizing the toxidromic approach ina tertiary care hospital in Uttar Pradesh. Material & Methods We had done an observational study on acutepoisoning patients presenting in the Emergency, Medicine, and Pediatrics department of Dr RMLIMS fromJanuary 2020 to January 2021.All consenting patients of both sexes with suspected poisoning were studied.Toxidromic approach based on clinical presentation of poisoned patients was utilized in identification ofthe type of poisoning. Observations & Results –total 82 cases were studied, we came across a total of 82poisoning cases seen over a period of 1 year in the emergency, medicine and paediatric wards of RMLIMS.There were 40 males and 42 females, with Cluster A containing 28 males and 27 females, whereas ClusterB had 12 males and 15 females, The relative risk and Odd’s ratio of total cases came out as 0.49 and 0.45respectively. Majority of the cases in Cluster A &B showed features of Cholinergic Toxidrome, followedby corrosives and sympatholytics, anticholinergic toxidromes and medical toxins. Conclusion: we needto develop appropriate medical facilities like extracorporeal membrane oxygenation (ECMO) as a rescuemodality for patients with acute reversible life threatening cardiopulmonary conditions. Poison control centrewith Analytical Toxicology laboratory should be developed to handle and assist in advising the specific andappropriate management of poisoning cases.